2016
DOI: 10.1002/chem.201603775
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Grip: Magnesium Complexes with a Phosphine‐Modified Phosphonium Diylidic Lewis Base

Abstract: Simple strategies to obtain magnesium complexes with the soft chelating diylidic ligand [Ph PCHPPh (fluorenylidene)] (dppmflu ) were developed to evaluate the influence of the hard acid (cation) and soft base (anion) mismatch on the stability and reactivity of the formed derivatives. Deprotonation of the precursor Ph PCH PPh (flu) (dppmfluH) by an alkylmagnesium derivative or magnesium amide provided access to [{Mg(dppmflu)(μ-nBu)} ], [Mg(dppmflu){N(SiMe ) }], and [{Mg(dppmflu)(μ-Me)} ], which were used as sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 118 publications
0
22
0
2
Order By: Relevance
“…Langer et al reported very recently an Mg complex with an intramolecular coordinating phosphine group that acts as a masked FLP (Scheme ) . Due to a hard/soft mismatch, the P–Mg bond is weak and can be easily cleaved by THF coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Langer et al reported very recently an Mg complex with an intramolecular coordinating phosphine group that acts as a masked FLP (Scheme ) . Due to a hard/soft mismatch, the P–Mg bond is weak and can be easily cleaved by THF coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Multinuclear magnesium hydride complexes [1][2][3][4][5][6][7][8][9][10] are being increasingly studied as molecular model systems for the hydrogen storage material [MgH 2 ] 1 .O ther interest in such complexes stems from their use as potent hydride sources in synthesis and their recognition as key intermediates in early main-group metal catalysis. [11] Starting from am agnesium alkyl or amide complex, typical synthetic routes involve metathesis with silane hydride reagents.Other routes include cyclohexadiene [12] or alane [13] induced hydrogenation of an Mg I complex or b-hydride elimination of am agnesium amidoborane species.…”
mentioning
confidence: 99%
“…[9] While hard chelating Lewis bases are obviously preferred for the stabilization of such oligonuclear entities,s ome magnesium hydride clusters feature unusual soft-hard ligand-Mg contacts,s uch as IPr···Mg or P···Mg contacts in Mg 4 H 6 (IPr) 2 [N(SiMe 3 ) 2 ] 2 and Mg 4 H 4 [N(DIPP)PPh 2 ], respectively.W erecently reported on the isolation and structure of [MgH(dppmflu)(THF)] 2 using al igand exclusively based on soft donors. [10] Inspired by the efficient bonding of soft ligands to hard Mg 2+ centers,w ei ntroduce an alternative concept for the kinetic stabilization of magnesium hydride clusters.R ather than using as terically encumbered, rigid ligand with ap redetermined, strongly binding nitrogen donor set, we reasoned that the use of flexible donors,s uch as hybrid ligands containing ac ombination of hard and soft donor atoms in close proximity,s hould be able to stabilize ag rowing magnesium hydride fragment by adapting its coordination mode.W hereas rigid and bulky DIPPnacnac ligands may stabilize magnesium hydride clusters through prevention of ligand exchange by steric shielding,use of asofter chameleontype ligand system with abroad variety of coordination modes guarantees efficient bonding to the large diversity of Mg 2+ centers at any stage of ag rowing magnesium hydride aggregate,t hus preventing precipitation of [MgH 2 ] 1 from the highly dynamic reaction mixture.…”
mentioning
confidence: 99%
See 2 more Smart Citations